2015 IEEE International Conference on Bioinformatics and Biomedicine (BIBM) 2015
DOI: 10.1109/bibm.2015.7359895
|View full text |Cite
|
Sign up to set email alerts
|

Usability testing of a novel automated external defibrillator user interface: A pilot study

Abstract: High quality CPR in conjunction with early defibrillation can enhance survival outcomes following cardiac arrest. This usability study aimed to evaluate a novel prototype user interface of a public access defibrillator for the improvement of CPR during a simulated resuscitation attempt. Test candidates were asked to use the device in the absence of audible instructions, relying solely on the device membrane, to perform CPR chest compressions. The rate of the rescuer chest compression were then assessed and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Despite the minimal training requirements, studies have shown that people struggle to use AEDs correctly for several reasons such as not hearing the instructions, assuming that the device can only be used by trained personnel, and misunderstanding where to place the shock pads, among other issues [70,71]. AEDs would benefit from further usability evaluation and design refinement due to the reported use errors and its public health impact.…”
Section: Product and Use Case Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the minimal training requirements, studies have shown that people struggle to use AEDs correctly for several reasons such as not hearing the instructions, assuming that the device can only be used by trained personnel, and misunderstanding where to place the shock pads, among other issues [70,71]. AEDs would benefit from further usability evaluation and design refinement due to the reported use errors and its public health impact.…”
Section: Product and Use Case Scenariomentioning
confidence: 99%
“…However, implementing this in a web-based platform is expected to yield different outcomes, as the mouse clicking is less physically strenuous than the actual chest compression, and can lower the user's attention and focus on the activity, thereby impacting the reasons time. To account for this predicted outcome, the CPR performance time for subjects was reduced to 30 s. Boundaries depicting too-slow or too-fast compression rates were determined from the Samaritan PAD 450p manual [70]. An early mockup was created to assist with the planning of the feature.…”
Section: User Input-pushing Buttonsmentioning
confidence: 99%
“…A rigorous test protocol was jointly developed by consortium members, led by usability testers from Ulster University's UX Lab. The usability testing protocol was informed by Ulster's UX-Lab having carried out a range of usability tests on medical devices, software and data visualisations [6][7][8][9][10][11][12][13][14][15][16] (see Fig. 3).…”
Section: Formative Evaluationmentioning
confidence: 99%